Efficient ferulic acid and xylo-oligosaccharides production by a novel multi-modular bifunctional xylanase/feruloyl esterase using agricultural residues as substrates. (February 2020) - Wang, Ruonan; Yang, Jinshui; Jang, Jin Myong; Liu, Jiawen; Zhang, Yu; Liu, Liang; Yuan, Hongli
Highlights: A novel bifunctional xylanase/feruloyl esterase (rXyn10A/Fae1A) was obtained. The highest ferulic acid yield (7.31 mg/g substrate) was produced by rXyn10A/Fae1A. Inter-domain synergism of rXyn10A/Fae1A is essential for the release of ferulic acid. Recombinant E. coli was constructed and secreted the bifunctional enzyme out of cells. Co-production of ferulic acid and XOSs during the cultivation of recombinant E. coli . Abstract: Liberating high value-added compounds ferulic acid (FA) and xylo-oligosaccharides (XOSs) from agricultural residues is a promising strategy for the utilization of lignocellulose. In this study, a bifunctional xylanase/feruloyl esterase from bacterial consortium EMSD5 was heterogeneously expressed in Escherichia coli . Depending on the inter-domain synergism of the recombinant enzyme rXyn10A/Fae1A, high yields of FA (2.78, 1.82, 1.15 and 7.31 mg/g substrate, respectively) were obtained from 20 mg in-soluble wheat arabinoxylan, de-starched wheat bran, ultrafine-grinding corn stover and steam-exploded corncob. Meanwhile, 3.210, 1.235, 1.215 and 0.823 mg xylose/XOSs were also released. For cost-saving enzyme production, we firstly constructed a recombinant E. coli, which could secrete the bifunctional xylanase/feruloyl esterase out of cells. When the recombinant E. coli was cultured in medium containing 200 mg de-starched wheat bran, 474 μg FA and 18.2 mg xylose/XOSs were also detected. Hence, rXyn10A/Fae1A and the recombinant strain showed great applied potential for FA and XOSs production.